Comparison of Masculine and Feminine Gender Roles in Iranian Patients with Gender Identity Disorder - Kaveh Alavi, MD; Mehrdad Eftekhar, MD; Amir Hossein Jalali Nadoushan, MD (Sexual Medicine, 2015)
Introduction: Gender identity disorders (GID) are heterogeneous disorders that may be influenced by culture and social norms. Aim: The aim of this study was to determine masculine and feminine gender roles in a group of Iranian patients with GID and compare these roles with two control groups. Methods: Twelve male‐to‐female (MF) and 27 female‐to‐male (FM) individuals with GID referred to Tehran Psychiatric Institute in Tehran, I. R. Iran were evaluated by self‐report inventories and were compared with two groups of healthy controls (81 men and 89 women). Diagnoses were established based on the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM‐IV) criteria. Data analysis was done using analysis of variance and chi‐squared test. Main Outcome Measures: Masculine and feminine gender roles were assessed by two questionnaires: (i) Gender‐Masculine (GM) and Gender‐Feminine (GF) scales derived from the Minnesota Multiphasic Inventory‐2 (MMPI‐2); (ii) Bem Sex Role Inventory (BSRI). Results: In the scales of masculinity, MF‐GID individuals scored as male controls, but lower than female controls. FM‐GID individuals scored similar to female controls and higher than male controls. In femininity scales, MF‐GID individuals and control women seemed similar, and both scored higher than the other groups. FM‐GID persons were considered less feminine than both controls in the GF scale of MMPI‐2, but not in the BSRI. In both scales, FM‐GID persons had higher scores than control women and MF‐GID individuals. Conclusion: Iranian FM‐GID individuals were less feminine than normal men. However, MF‐GID individuals were similar to normal women or more feminine. Cultural considerations remain to be investigated. Alavi K, Eftekhar M and Jalali Nadoushan AH. Comparison of masculine and feminine gender roles in Iranian patients with gender identity disorder. Sex Med 2015;3:261–268.